Supplementation of Turmeric Flour (Curcuma longa) in Feed from The Grower to Laying Phase on The Productivity of Mojosari Ducks - Mappanganro, Rasyidah; Ananda, Suci; Mappanganro, Nurlailah; Ardiansyah, Widiastuti; Mohammed, Yousif Altaher Edress (Hasanuddin Journal of Animal Science (HAJAS), 2024)
This research aims to determine the performance of the grower phase until the first egg laying of mojosari ducks given turmeric flour supplementation. This research used 40 mojosari ducks aged 16-28 weeks. The experimental research method used a completely randomized design with five treatments and four replications. The study was carried out for 12 weeks, maintained intensively, and given basal feed with the addition of 0.2%, 0.4%, 0.6%, and 0.8% turmeric flour. Basal feed is made from fine bran, ground corn, and concentrate. The parameters observed were the final weight of the growth phase, body weight gain, feed conversion in the growth phase, body weight and age at first egg laying, and the weight of the first egg. The data obtained was then analyzed using analysis of variance (ANOVA) and Pearson correlation. The results showed that adding turmeric flour at 16-24 weeks of age was able to increase body weight gain and reduce feed conversion rate (p<0.05), and at 24-28 weeks of age could accelerate the age of first egg laying (p<0.01). Pearson correlation showed that there was a positive relationship (0.462) between age at first laying and first egg weight, a negative relationship (-0.569) between age at first laying and body weight, and a negative relationship (-0.398) between duck body weight and first egg weight. Adding 0.6% turmeric flour to feed is the optimal and best level to improve the performance of mojosari ducks from the growth phase to the egg-laying phase. Keywords: Grower, laying, Mojosari duck, turmeric flour